THE ROLE OF MYOGENIC CONSTRICTION IN HYPERTENSION AND CHRONIC KIDNEY DISEASE - Nademi, Samera (My University, 2022)
Chronic kidney disease (CKD) is defined as glomerular filtration rate (GFR) less than 60 mL/min/1.73 m2 for 3 months and is characterized by progressive loss of renal function. The second leading cause of CKD is hypertension. More than half of CKD patients also suffer from hypertension. Arteries and arterioles adjust to the fluctuations in the systematic blood pressure through a mechanism called autoregulation. In the kidneys, autoregulation protects the delicate glomeruli capillaries from high blood pressure and occurs through myogenic constriction (MC). MC refers to contraction of arterioles in response to an increase in the blood pressure. Chronically hypertensive individuals and animal models have an enhanced MC, leading to minimal renal injury despite their elevated blood pressure. Experimental and clinical evidence point to a role for the MC in the pathogenesis of the CKD, however, the mechanism through which preglomerular arterial MC contributes to CKD has not been fully elucidated. This thesis showed that augmented MC in chronically hypertensive animal models was due to increased thromboxane A2 prostaglandin that was not released from the endothelium (Chapter 2). Nevertheless, inhibiting MC while also reducing the blood pressure prevented salt-induced renal injury even though the blood pressure was still not normalized compared to the normotensive controls (Chapter 3). The resulting improvement in renal structure and function could be attributed to the reduction in the blood pressure, albumin, and uromodulin (UMOD) excretion (Chapter 3). UMOD is a kidney-specific glycoprotein that, based on a genome-wide association study have the strongest association to CKD (Chapter 3). Comparing two CKD hypertensive animal models further revealed that CKD progression was independent of the blood pressure and strongly associated with UMOD excretion levels (Chapter 4). Collectively, the data discussed in this thesis demonstrates potential therapeutic targets in CKD hypertensive animal models.
MYOGENIC CONSTRICTION: ITS REGULATION, ROLE IN HYPERTENSIVE KIDNEY DISEASE, AND ASSOCIATION WITH URINARY UROMODULIN
Keywords: Chronic Kidney Disease, Hypertension, Myogenic Constriction, DSS, SHR, WKY, BN13, Old, Older, Salt Sensitivity, Uromodulin, Proteinuria, Albuminuria, Renal Autoregulation, Preglomerular Arteries, Arcuate arteries, afferent arteriole, Prostaglandin, Thromboxane A2, Nitric Oxide, Endothelium, Nifedipine, High Salt, Uromodulin, Protein Casts